KARAKTERISTIK DOMBA LOKAL PALU BERDASARKAN KERAGAMAN MORFOMETRIK - Amiruddin Dg. Malewa; Salmin Salmin (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Sheep is one of the preeminent commodities of Central Sulawesi in term of natural/pastural resources, climatic and cultural social condition. All varieties of local sheep in Central Sulawesi were generated from a cross-breeding between Fat-tail sheep (FTS) and Merbas sheep. The research was aimed at identifying the sheep phenotype characteristics as the criteria for sheep selection. The study was carried out in Palu city, and Biromaru sub district of Central Sulawesi from February to May and from November to December 2006. Data of sheep body sizes were collected from three different sites: Poboya (East Palu), Kawatuna (South Palu) and Loru (Biromaru). A total number of 412 sheep from the three sites were used and then randomly selected to obtain 102 (24%), 122 (10%), and 56 (28%) adult sheep from Poboya, Kawatuna and Loru, respectively. The research results showed that the local sheep population has been steadily decreased every year and currently there have been only 3270 sheep remained.  Among the three sites, the highest body weight of sheep was found with those from Biromaru. The average of birth weight,  weaning,  adult  males  and  females  body  were  3.25±0.53  kg,  11.25±3.33  kg,  42.00±6.245  kg,  and  30.14±6.28  kg, respectively. The body size of 18-24 month old sheep from Biromaru was also higher than those from the other sites.  Whereas for 36 month old sheep, those from  East Palu and Biromaru  were higher than those  from South Palu. The principal  Component Analysis (PCA) showed that the best criteria for sheep selection were breast diameter, body length, height of hip, and wide of tail.